Kualitas Organoleptik Telur Itik yang Diberi Pakan Maggot Hidup (Hermetia illucens) - Aam Gunawan (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
Maggot black soldier fly (Hermetia illucens) is a protein source of feed which is highly favored by poultry, especially ducks and chickens. However, it is feared that the provision of live maggot in ducks will affect the organoleptic quality of the egg, especially its taste and aroma. Therefore this study aims to determine the organoleptic quality of duck eggs fed Hermetia illucens maggot feeds in a living state. The study used 120 alabio ducks which were placed in a postal cage. The design used was a completely randomized design, each treatment using six replications. Each replication is taken egg sample to be tested panelists. The panelists used were 67 panelists who were somewhat trained. The data obtained were analyzed of variance and Duncan's multiple range test. The treatments that were tried consisted of P1: low protein rations without live maggot, P2: low protein rations with live maggot administration 40 g/bird/day, P3: high protein rations without live maggot administration, and P4: high protein rations with live maggot administration 40g/bird/day. The results showed that the treatment affected the texture, flavor, and aroma of boiled eggs. Ducks fed with high protein ration coupled with the provision of live maggot 40 g/bird/day produce softer textures, tastes quite good, and aroma more fishy. Keywords: Maggot, duck eggs, organoleptics